A consideration of starch and protein digestive dynamics in chicken-meat production. Issue 2 (3rd June 2015) - LIU, S.Y.; SELLE, P.H.
Abstract : The hypothesis that glucose and amino acids should be made available in appropriately balanced quantities at the sites of protein synthesis for efficient protein deposition and growth performance is not new in animal nutrition. The objective of this review is to consider starch and protein digestive dynamics in light of recent developments and research outcomes in relation to chicken-meat production. This will concentrate on the concept that catabolism of amino acids in enterocytes provides energy for the gut and slowly digestible starch benefits performance. These are supported by relatively recent developments and studies with reducing agents. Practices such as whole grain feeding, hydrothermally processing diets, addition of exogenous enzymes and synthetic amino acids to broiler diets modify starch and protein digestive dynamics. It may be possible to enhance feed conversion efficiency of broiler chickens by manipulating starch and protein digestive dynamics and likelihood of using these methods is considered in this review.